Biomarkers of Brain Injury in the Premature Infant - Douglas-Escobar, Martha V.; Weiss, Michael D. (Frontiers in Neurology, 2013)
The term “encephalopathy of prematurity” encompasses not only the acute brain injury (such as intraventricular hemorrhage) but also complex disturbance on the infant’s subsequent brain development. In premature infants, the most frequent recognized source of brain injury is intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL). Furthermore 20-25% infants with birth weigh less than 1,500 g will have IVH and that proportion increases to 45% if the birth weight is less than 500-750 g. In addition, nearly 60% of very low birth weight newborns will have hypoxic-ischemic injury. Therefore permanent lifetime neurodevelopmental disabilities are frequent in premature infants. Innovative approach to prevent or decrease brain injury in preterm infants requires discovery of biomarkers able to discriminate infants at risk for injury, monitor the progression of the injury and assess efficacy of neuroprotective clinical trials. In this article, we will review biomarkers studied in premature infants with IVH, Post-hemorrhagic ventricular dilation (PHVD) and PVL including: S100b, Activin A, erythropoietin, chemokine CCL 18, GFAP and NFL will also be examined. Some of the most promising biomarkers for IVH are S100β and Activin. The concentrations of TGF-β1, MMP-9 and PAI-1 in cerebrospinal fluid could be used to discriminate patients that will require shunt after post-hemorrhagic ventricular dilation. Neonatal brain injury is frequent in premature infants admitted to the neonatal intensive care and we hope to contribute to the awareness and interest in clinical validation of established as well as novel neonatal brain injury biomarkers.